Treatment with a Monoclonal Anti-IL-12p40 Antibody Induces Substantial Gut Microbiota Changes in an Experimental Colitis Model - Josué Castro-Mejía; Maja Jakesevic; Łukasz Krych; Dennis S. Nielsen; Lars H. Hansen; Bodil C. Sondergaard; Peter H. Kvist; Axel K. Hansen; Thomas L. Holm (Gastroenterology Research and Practice)
Background and Aim. Crohn’s disease is associated with gut microbiota (GM) dysbiosis. Treatment with the anti-IL-12p40 monoclonal antibody (12p40-mAb) has therapeutic effect in Crohn’s disease patients. This study addresses whether a 12p40-mAb treatment influences gut microbiota (GM) composition in mice with adoptive transfer colitis (AdTr-colitis). Methods. AdTr-colitis mice were treated with 12p40-mAb or rat-IgG2a or NaCl from days 21 to 47. Disease was monitored by changes in body weight, stool, endoscopic and histopathology scores, immunohistochemistry, and colonic cytokine/chemokine profiles. GM was characterized through DGGE and 16S rRNA gene-amplicon high-throughput sequencing. Results. Following 12p40-mAb treatment, most clinical and pathological parameters associated with colitis were either reduced or absent. GM was shifted towards a higher Firmicutes-to-Bacteroidetes ratio compared to rat-IgG2a treated mice. Significant correlations between 17 bacterial genera and biological markers were found. The relative abundances of the RF32 order (Alphaproteobacteria) and Akkermansia muciniphila were positively correlated with damaged histopathology and colonic inflammation. Conclusions. Shifts in GM distribution were observed with clinical response to 12p40-mAb treatment, whereas specific GM members correlated with colitis symptoms. Our study implicates that specific changes in GM may be connected with positive clinical outcomes and suggests preventing or correcting GM dysbiosis as a treatment goal in inflammatory bowel disease.